2019
DOI: 10.3892/etm.2019.8082
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biochemical investigations of key antioxidant/oxidant molecules in Saudi patients with recurrent miscarriage

Abstract: The present study was undertaken to: i) Determine the levels of oxidative stress (OS) markers, malondialdehyde (MDA), superoxide anions (SOA) and hydrogen peroxide (H2O2), in both plasma and placental tissues of recurrent miscarriage (RM) patients in comparison with those of healthy pregnant (HP) and non-pregnant (NP) women; ii) determine the levels of enzymatic antioxidants [glutathione peroxidase (GPx), glutathione reductase (GSR), superoxide dismutase (SOD) and catalase (CAT)], and non-enzymatic antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 61 publications
(88 reference statements)
4
21
0
1
Order By: Relevance
“…A recent study reported significant increase of SOA in plasma samples of RPL patients compared to the control samples (45.2 ± 6.10 nmol/ml vs 35.3 ± 5.45 nmol/ml). Similar difference was observed for the placental tissue SOA between the two groups (5.93 ± 0.78 µmol/min/mg in RPL patients and 4.67 ± 0.62 µmol/min/mg in healthy pregnant women) [ 8 ].…”
Section: Main Textsupporting
confidence: 79%
See 4 more Smart Citations
“…A recent study reported significant increase of SOA in plasma samples of RPL patients compared to the control samples (45.2 ± 6.10 nmol/ml vs 35.3 ± 5.45 nmol/ml). Similar difference was observed for the placental tissue SOA between the two groups (5.93 ± 0.78 µmol/min/mg in RPL patients and 4.67 ± 0.62 µmol/min/mg in healthy pregnant women) [ 8 ].…”
Section: Main Textsupporting
confidence: 79%
“…Reported plasma MDA levels were 5.95 ± 0.91 pM for recurrent miscarriage patients and 5.12 ± 0.81 pM for healthy controls [ 9 ]. Similarly in another study, placental MDA levels were highly significantly increased in recurrent miscarriage subjects compared to the controls (334 ± 45.8 nmol/g wet weight versus 258 ± 35.7 nmol/g wet weight) [ 8 ].…”
Section: Main Textmentioning
confidence: 75%
See 3 more Smart Citations